FARMERS PARTICIPATION IN INTEGRATED PEST CONTROL OF RICE (Oryza sativa L.) IN JAMANIS DISTRICT, TASIKMALAYA REGENCY WEST JAVA PROVINCE: PARTISIPASI PETANI DALAM PENGENDALIAN HAMA TERPADU TANAMAN PADI (Oryza sativa L.) DI KECAMATAN JAMANIS KABUPATEN TASIKMALAYA PROVINSI JAWA BARAT - Ubaidillah Hamzah; Achdiyat (Jurnal Penyuluhan Pertanian, 2022)
This study aims to describe farmer participation and analyze factors related to farmer participation in integrated pest control of rice (Oryza sativa L.). The research was conducted in Jamanis District, Tasikmalaya Regency, West Java Province. Data analysis using descriptive analysis and chi-square. The measurement method uses a Likert modification. Primary data was generated by questionnaire with a research sample of 77 respondents. The independent variables consist of internal factors (age, education, farm area, farming experience, farmer motivation) and external factors (role of extension workers to farmer group functions). The dependent variable consists of farmers' participation in decision making, implementation of activities, evaluation, and utilization of activities. The results showed that farmer participation was in the medium category with a percentage of 44.16%, the low category with 40.26%, and the high category with 15.58%. Factors that determine farmer participation are the role of extension workers and the function of farmer groups as a vehicle for cooperation.